Intraosseous carcinoma of the jaws: A clinicopathologic review. part II: Odontogenic carcinomas. Issue 6 (31st January 2012) - Woolgar, Julia A.; Triantafyllou, Asterios; Ferlito, Alfio; Devaney, Kenneth O.; Lewis, James S.; Rinaldo, Alessandra; Slootweg, Pieter J.; Barnes, Leon; W. Eisele, David
Abstract This is the second of a 3‐part review of the clinicopathologic features of intraosseous carcinoma of the jaws (IOCJ). This part deals with odontogenic carcinomas, rare entities that are difficult to evaluate because of changes in classification/nomenclature, lack of standardized diagnostic criteria, and variable consistency of the existing literature. Endorsing a critical approach, problems are addressed and areas of uncertainty are highlighted. As in part I, we emphasize histopathologic features from a diagnostic point of view and also question the existence of some "distinct" entities. © 2012 Wiley Periodicals, Inc. Head Neck, 2012